Sinorhodeus microlepis, a new genus and species of bitterling from China (Teleostei: Cyprinidae: Acheilognathinae) - Li, Fan; Liao, Te-Yu; Arai, Ryoichi; Zhao, Liangjie (Zootaxa, 2017)
A new genus and species, Sinorhodeus microlepis gen. et sp. nov., is described from a tributary of the Yangtze River, in Chongqing City, China. Sinorhodeus gen. nov. can be distinguished from four closely related genera, Paratanakia, Pseudorhodeus, Rhodeus, and Tanakia, by the following combination of characters: pharyngeal teeth 0,0,4–4,0,0, longitudinal scales 41–46, white spots on dorsal-fin rays absent, a black blotch on dorsal fin in juvenile absent, and less developed wing-like yolk sac projections in larvae. Phylogenetic analysis of one mitochondrial gene and six nuclear genes supports the establishment of the new genus.